(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Today, one of the most common stomatological diseases is periodontitis, which is an inflammatory disease of the gums, which over time leads to atrophy of bone and connective tissue of the gums, resulting in tooth decay and spontaneous loss of teeth. In general, bad habits and general diseases, smoking, diabetes, gastrointestinal diseases, diseases of the cardiovascular system, stress, squeezing the gums due to the formation of alloy stones around the teeth, defects in the development of the jaw and palate, improper growth of teeth, teeth It is caused by diseases such as crooked position and mouth breathing.